Faktor Risiko Perdarahan Gastrointestinal pada Pasien dengan Sindrom Koroner Akut: Sebuah Tinjauan Sistematis - setyobudi, Assyadilla Kirana; Vidyani, Amie; Sutadji, Jonathan Christianto; Kurniawati, Lady Aqnes; Suhardi, Kevin Fernando (Jurnal Penyakit Dalam Indonesia, 2026)
Introduction. Gastrointestinal bleeding (GIB) is a serious but potentially preventable condition. Its symptoms include hematemesis, hematochezia, and melena. Risk factors for GIB include medications such as antiplatelets and anticoagulants, which are standard treatments for acute coronary syndrome (ACS). GIB is strongly associated with ACS and represents the most common bleeding complication in these patients. This study aimed to systematically review the factors contributing to GIB in patients with ACS. Methods. Relevant articles were retrieved from PubMed, ScienceDirect, Springer, and EBSCO databases, covering studies on GIB risk factors in ACS patients published between March 31, 2003, and March 31, 2025. The search was conducted using specific keywords and Boolean operators. Data were then extracted and comprehensively evaluated. Results. A total of 17 studies were included, with varied patient populations, including general ACS patients, as well as those specifically diagnosed with acute myocardial infarction (AMI), ST-elevation myocardial infarction (STEMI), or non-ST-elevation myocardial infarction (NSTEMI). The follow-up periods ranged widely, from 15 days to 4 years. Based on the initial evaluation, 23 potential risk factors were identified. GIB was more likely to occur in older individuals, females, and those with a history of smoking and alcohol consumption. Comorbidities, including anemia, diabetes, peptic ulcer disease, cirrhosis, and chronic kidney disease, were also more frequently observed among ACS patients with GIB events. The use of proton pump inhibitors (PPIs) was identified as the only protective factor. Conclusion. This systematic review identified several risk factors associated with GIB in ACS patients. Careful monitoring and appropriate management should be implemented in patients with these risk factors to prevent bleeding events, which may be fatal.